Nailfold capillaroscopy in common non-rheumatic conditions: A systematic review and applications for clinical practice - Ciaffi, Jacopo; Ajasllari, Nerenxa; Mancarella, Luana; Brusi, Veronica; Meliconi, Riccardo; Ursini, Francesco (Microvascular research, 2020)
The role of nailfold capillaroscopy (NC) in common non-rheumatic conditions has not been systematically reported. The aim of this review is to outline NC features observed in frequent non-rheumatic conditions, providing a practical tool to support rheumatologists for the interpretation of capillaroscopic abnormalities in patients with no established connective tissue disease (CTD). We undertook a systematic search in PubMed and Web of Science databases. Studies reporting adults or children with common non-rheumatic diseases or conditions in which quantitative and/or qualitative assessment of morphological nailbed capillary findings was obtained, were included. The presence of a control group composed by subjects not affected by the studied condition and direct comparison of findings between groups were needed. We included 25 articles. Diabetes mellitus (11 studies), glaucoma (7 studies) and essential hypertension (3 studies) were the most represented diseases. Reduced capillary density, tortuosity, dilated capillaries, microhaemorrhages, ramified capillaries and avascular areas can be observed in diabetic patients. Association was reported between poor glycaemic control or longer duration of diabetes, or presence of microvascular complications as retinopathy and neuropathy, and more severe capillaroscopic abnormalities. Decreased capillary density, tortuosity, microhaemorrhages, dilated capillaries, avascular areas and ramifications might also be present in glaucoma, while in essential hypertension a reduced capillary density might be expected. Abnormal capillaroscopic findings are not uncommon even in individuals with no CTD. Therefore, presence of comorbidities known to potentially affect the microvascular array should always be investigated in patients undergoing NC and the interpretation of findings might be weighted accordingly. •Nailfold capillaroscopy has protean applications beyond rheumatic diseases.•Patients with diabetes or glaucoma present nailbed microvascular abnormalities.•Findings referable to scleroderma pattern are not rare in non-rheumatic diseases.•Medical history might help to avoid misinterpretation of capillaroscopic features.